Neuromuscular training warm-up prevents acute non-contact lower extremity injuries in children’s soccer. A cluster randomized controlled trial. - Hilska, Matias (My University, 2021)
Physical activity during childhood is widely beneficial for overall health but participation in sports also entails a high risk for injuries. Prevention of sports injuries is essential in youth as injuries are associated with lesser future physical activity and thus greater all-cause morbidity. The aim of this study was to examine whether a neuromuscular training warm-up program can reduce the risk for acute lower extremity (LE) injuries in children’s U11-U14 soccer. Twenty top-level U11-U14 soccer clubs (N=1403 children) in Finland were randomized into intervention and control groups and followed-up for 20 weeks. The intervention group team coaches were introduced to a neuromuscular training warm-up to replace standard warm-up 2-3 times a week. The control teams were asked to perform their standard warm-up. The main outcome measure was a soccer-related acute LE injury and the secondary outcome measure was an acute non-contact LE injury. Altogether 656 acute LE injuries occurred (310 in the intervention and 346 in the control group) and 46% of these injuries were non-contact by mechanism. Overall acute LE injury incidence was similar between groups: 4.4 injuries / 1000 hours of exposure in the intervention group and 5.5 / 1000 hours of exposure in the control group. In acute non-contact LE injuries, a significant 32% reduction in injury incidence in favor of the intervention group was observed. A neuromuscular training warm-up operated by team coaches was found to be effective in preventing acute non-contact LE injuries and is encouraged to be implemented as part of weekly practice in children’s soccer.
Keywords: liikuntavammojen ehkäisy, lasten jalkapallo, hermo-lihasjärjestelmää aktivoiva harjoittelu